Pengaruh Pemahaman Bacaan Alquran Terhadap Kualitas Keimanan Studi Analisis Islamic Center Medan - Adinda, Nurul (UIN Sumatera Utara, 2024)
This research is entitled The effect of reading comprehension of the Koran on the quality of faith of Santri Analysis Studies at the Islamic Center of Medan. The discussion about the Islamic Center focuses on Madrasah Tsanawiyah Hifzhil Quran, which incidentally is the reader and memorizer of the Koran. The condition of the Hifzil Qur'anic students is that reading the Qur'an does not reach them, but only until the reading is fluent. Because what they read does not match what they practice. Remembering the hadith of Rasulullah SAW will come out of my ummah, when reading the Qur'an does not reach his heart, but only reaches his throat. (H.R. Bukhari), so that it can reduce or damage the quality of students' faith.With the above discussion, I formulate the discussion and the goal is to find out how the obligation of students to read and understand the reading of the Koran and to find out how students practice the values of reading the Koran, to increase faith in the Islamic Center Medan.The method used in this study is through field research (Fiel Research) with a qualitative approach, data collection techniques are processed from direct observations with field interviews, with a total of three informants and documentation, data analysis is carried out using descriptive analysis, which includes collecting data, filtering, classifying data and drawing conclusions.The results of research conducted at the Islamic Center focused on Madrasah Tsanawiyah Hifzhil Quran is the obligation of students to the Koran only to deposit, without paying attention to tajwid and makharijul letters, and what they read is not in accordance with what they are doing, prioritizing quantity over quality, reading quality students are below average, and they understand only one percent of the Quran they read, because they do not know how to practice it, and the method they use is the talaqqi method.